2017
DOI: 10.1038/nrc.2017.109
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mutant p53 for efficient cancer therapy

Abstract: The tumour suppressor gene TP53 is the most frequently mutated gene in cancer. Wild-type p53 can suppress tumour development by multiple pathways. However, mutation of TP53 and the resultant inactivation of p53 allow evasion of tumour cell death and rapid tumour progression. The high frequency of TP53 mutation in tumours has prompted efforts to restore normal function of mutant p53 and thereby trigger tumour cell death and tumour elimination. Small molecules that can reactivate missense-mutant p53 protein have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
553
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 737 publications
(592 citation statements)
references
References 157 publications
6
553
0
2
Order By: Relevance
“…It is well known that WT p53 protein is usually maintained at low levels . However, the p53 mutant phenotype leads to abnormal p53 stabilization and mutant p53 protein overexpression . Consistent with this, our study using two independent CRC cohorts suggested that HMGA2 was prognostic among p53‐negative patients who were highly likely to have WT p53 ( TP53 ) genes.…”
Section: Discussionsupporting
confidence: 87%
“…It is well known that WT p53 protein is usually maintained at low levels . However, the p53 mutant phenotype leads to abnormal p53 stabilization and mutant p53 protein overexpression . Consistent with this, our study using two independent CRC cohorts suggested that HMGA2 was prognostic among p53‐negative patients who were highly likely to have WT p53 ( TP53 ) genes.…”
Section: Discussionsupporting
confidence: 87%
“…However, little is known about the function of b3 subunit in tumor. p53 is a cellular stress sensor that triggers transient cell cycle arrest, permanent cell cycle arrest, cellular senescence, and apoptosis [41]. b3 may be a direct target of transcriptional activation by p53 and involved in a proapoptotic pathway through the endoplasmic reticulum in T98G and Saos2 cell lines as described previously [23].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor suppressor p53 is a crucial coordinator in cellular responses to stress from oncogene activation, DNA damage, and hypoxia [79, 80]. The antiproliferative capability of p53 mediates cell cycle arrest, apoptosis, and even cellular senescence [81, 82].…”
Section: Substrates Of Huwe1mentioning
confidence: 99%